Thermographic investigation of ultrasonically induced temperature distribution in tissues and tissue-equivalent phantoms - PASHOVKIN, T.; KHIZNYAK, E.; SARVAZYAN, A. (Archives of Acoustics, 1984)
The purpose of the paper was to develop a computerised thermographic method for the investigation of the temperature fields in tissue phantoms irradiated by ultrasound and to study heating patterns in sonicated heterogeneous and homogeneous phantoms. The developed thermographic system provided the possibility of obtaining threedimensional images of the temperature distributions in the irradiated samples. It is shown that the temperature pattern in the heterogeneous tissue phantoms irradiated by ultrasound can be dependent not only on the differences in bulk acoustical properties of the adjacent tissues but also on the differences in their shear properties.